ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTS PADA MATERI BENTUK ALJABAR - Fatimah Fatimah; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to analyze the mathematical communication skills of MTs students in Algebraic Forms. This research method used a qualitative descriptive method. The place of research was conducted in one of the Bandung City Middle Schools in class VII of the odd semester of the academic year 2018-2019. The population of this study was seventh grade students of Al-Amanah Bandung MTs in the material of Algebra Forms. The research subjects were class VII-a students. to obtain research data used test questions about the description. The results of the study concluded: (1) expressing daily events in mathematical language or symbols, (2) explaining ideas, situations and relationships, verbally and in writing by using algebraic expressions, (3) reading with understanding, a written percentage of mathematics , (4) connecting real objects, images, and diagrams into mathematical ideas